2020
DOI: 10.21608/ejhc.2020.74788
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Organizational Justice and Workplace Deviance Behavior among Staff Nurses

Abstract: Background: Organizational justice and workplace deviance behavior are the most important factors affecting the employees in each organization. When there was lack of fairness and support in the organization, staff tended to perform behaviors that damaging the organization. Aim: The study aimed at assessing the relation between organizational justice and workplace deviance behavior among staff nurses. Research design: A descriptive, correlational design was used. Setting: The study was conducted at Ain Shams U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…The phenomenon researched by Baig, and Ullah (2017) states that modern organizations are trying to gain competitive advantage through human power, unfortunately staff are involved in deviant activities in almost every organization and workplace deviance can be a major threat that can affect organizational efficiency, and some Most of these deviant practices are caused by unfair events that arise in the organization and ultimately reduce employee satisfaction. This is in line with research conducted by Abdullah and Marican (2017), which states that deviant behavior is a practice that is outside the normal norms of an organization [11].…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…The phenomenon researched by Baig, and Ullah (2017) states that modern organizations are trying to gain competitive advantage through human power, unfortunately staff are involved in deviant activities in almost every organization and workplace deviance can be a major threat that can affect organizational efficiency, and some Most of these deviant practices are caused by unfair events that arise in the organization and ultimately reduce employee satisfaction. This is in line with research conducted by Abdullah and Marican (2017), which states that deviant behavior is a practice that is outside the normal norms of an organization [11].…”
Section: Introductionsupporting
confidence: 91%
“…When rewards and penalties were introduced into an organization, the idea of organizational justice was first introduced. Later, it was expanded to include human relationships and interactions in addition to the same procedures and regulations [11]. Atkinson, et al, (2018), employees act abnormally to correct the situation if they believe their promises are not being kept.…”
Section: Social Exchange Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Rahman (2021) emphasised the importance of organisational justice on the efficiency of employees in an organisation. Further, Hany, Hassan and Badran (2020) showed that nurses' perceptions of organisational justice and workplace deviance are lower than the average. On the other hand, Gerlach (2019) shows that justice differentially impacts the quality and efficiency of the employee and employee-coworker relationships in the workplace.…”
Section: Organisational Justice and Workplace Deviancementioning
confidence: 99%